THE EFFECTS OF SOCIAL MEDIA ADVERTISING ON ENHANCING PURCHASE INTENTION: AN EMPIRICAL STUDY OF FACEBOOK ADVERTISING - Esther Elsemina S; Wijanto Wijanto; Rizal E. Halim (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2015)
This article focuses on Facebook Advertising and examine the effectiveness of the advertisements in enhancing customer’s purchasing intention in 2015. Five Construct of this article are Social Media Advertising, Brand Equity, Brand Image, Word of Mouth, and Purchase Intention. The investigation of this study can enable social media advertising to forecast the future  purchasing intention of customer.The statistical population included all undergraduate students will be the social media’s users in University of Indonesia. A conceptual model was developed and was tested using structural equation modeling and SPSS17.